Phonetics - Josipović Smojver, Višnja (Array, 2009)
This work presents phonetics as a scientific discipline: its subject matter, subdivision into three subdisciplines, methods and aims of research of each of them. Articulatory phonetics deals with the production of speech ; acoustic phonetics studies the transmission of speech ; and auditory phonetics focuses on speech reception. Two major categories of speech sounds are distinguished: consonants and vowels, and phonetic research often deals with suprasegmentals, features stretching over domains larger than individual sound segments. Phoneticians all over the world use a uniform system of notation, employing the symbols and following the principles of the International Phonetic Association. Present-day phonetics relies on sophisticated methods of instrumental analysis. Phonetics has a number of possible practical applications in diverse areas of life, including language learning and teaching, clinical phonetics, forensics, and various aspects of communication and computer technology.